Trend 1982 - 1996. Statistics Canada. CANSIM: Business, Consumer and Property Services - Information and Culture | Country: Canada | Province: Newfoundland and Labrador | Table: Summary statistics for firms providing computer services | Variable: All other expenses | Units: # Units x 1,000, 1982-1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-011. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Business, Consumer and Property Services - Information and Culture | Country: Canada | Province: Newfoundland and Labrador | Table: Summary statistics for firms providing computer services | Variable: All other expenses | Units: # Units x 1,000, 1982-1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-011. Dataset: Presents statistics on publishing (ie, newspapers, periodicals, books, software); motion pictures; video and sound recording (ie, motion picture and video production, post-production and distribution, and record production); computer systems design; data processing; and internet service providers in Canada and subnational geographies as available. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce, Prices, Consumption, and Cost of Living Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Newspapers, Information Industry, Publishing Industry, News Media, Book Publishers, Telecommunications Industry, Entertainment Industry